Measuring activity and participation in children and adolescents with disabilities: A literature review of available instruments. Issue 4 (9th June 2013) - Phillips, Rebecca L.; Olds, Tim; Boshoff, Kobie; Lane, Alison E.
Abstract : Background/aim: This article aims to (1) identify instruments available to measure activity and participation in children with disabilities; (2) describe the reliability and validity of these instruments; and (3) consider whether the available instruments capture the extent of involvement, as well as the difficulty and satisfaction/enjoyment associated with performance in all life areas. Method: A literature review was completed by undertaking an electronic search to identify instruments that measure activity and participation in children with disabilities. A further electronic search was conducted to obtain an adequate description of the instruments, including psychometric properties. Results: The search identified 20 instruments purporting to measure activity and participation, however, no single instrument measured extent of involvement, difficulty and satisfaction/enjoyment in all life areas. There were instances in which each of these aspects was captured, but not within the one instrument. Instruments assessed combinations of frequency, difficulty, assistance, environment and satisfaction across varying contexts, for example, school, domestic life, recreational tasks, leisure tasks or all life areas. Conclusions: Although a large number of instruments exist to measure varying aspects of activity and participation, there is currently no single instrument available to measure the extent of involvement, difficulty and satisfaction/enjoyment in all life areas. This finding indicates that there is the opportunity to develop a single instrument to measure activity and participation across all life areas.